Exploring breast cancer awareness and screening practices amongst rural women in The Gambia: Community-based cross-sectional study - Bakary Kinteh; Fatoumatta Jitteh; Mansour Badjie; Amadou Barrow; Lamin Jaiteh (PLoS ONE, 2025)
Background Breast cancer is a significant public health challenge in The Gambia, where it ranks as the second most commonly diagnosed cancer among women. Rural women face unique challenges in accessing screening services; however, evidence about their breast cancer awareness and screening uptake remains limited. This study aimed to assess breast cancer awareness and identify associated factors influencing screening uptake among rural women in The Gambia. Methods A community-based cross-sectional study was conducted among rural women in The Gambia. Using multistage sampling, we recruited 985 women from two local government authorities (response rate: 90.2%). Data were collected using a structured questionnaire administered in Kobo Toolbox. Descriptive statistics were used to summarize participant characteristics, while associations between predictors and breast cancer screening uptake were assessed using Chi-squared or Fisher’s exact test. Multivariable logistic regression was used to identify factors associated with screening uptake. Statistical significance was set at p<0.05 and adjusted odds ratios (aOR) with 95% confidence intervals were reported. Results The mean age of the study population was 32 years (standard deviation [SD]: ±12.6), with 34% aged 18–24 years. Although breast cancer awareness was high (87.7%), screening uptake was low (12.6%), primarily due to limited knowledge (58.7%), service unavailability (13.5%) and financial constraints (13.1%). Clinical breast examination was the most common screening method used (62.6%). Multivariable analysis revealed that Students (aOR=3.111, 95% CI: 1.453–6.663) and civil servants (aOR=2.778, 95% CI: 1.174–6.573) were more likely to undergo screening compared to unemployed women. Conversely, women with two (aOR=0.061, 95% CI: 0.005–0.791), three (aOR=0.075, 95% CI: 0.006–0.967), and five children (aOR=0.065, 95% CI: 0.005–0.877) were less likely to participate in screening compared to nulliparous women. Conclusion Despite the high awareness of breast cancer, screening uptake among rural women in The Gambia was notably low, primarily due to limited knowledge, service unavailability and financial constraints. There is an urgent need for targeted interventions to improve screening uptake, particularly among multiparous women in rural communities.